2021
DOI: 10.18502/ijrm.v19i11.9913
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxy vitamin D level and menstrual cycle length and regularity: A cross-sectional observational study

Abstract: Background: Research examining the role of vitamin D deficiency and the development of menstrual disorders in women is of widespread interest. Studies have been published showing that supplementation with high-dose vitamin D can lead to the restoration of the menstrual cycle. We lack adequate information regarding the effect of vitamin D levels on the physiology of menstruation and further on fertility in women of reproductive age due to the contradictory results reported by studies. Objective: To study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Singh et al found that women with regular menstrual cycles had notably elevated levels of vitamin D, whereas decreased levels of vitamin D were linked to a 13-fold increase in the likelihood of experiencing an irregular menstrual cycle [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Singh et al found that women with regular menstrual cycles had notably elevated levels of vitamin D, whereas decreased levels of vitamin D were linked to a 13-fold increase in the likelihood of experiencing an irregular menstrual cycle [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Indeed, many studies have shown that there is a relationship between vitamin D and mental health; individuals with insufficient vitamin D levels have a high risk of depression (Khan et al, 2022). Recently, many studies from around the world have shown that the menstrual cycle is also affected by vitamin D. For example, in 2021, a study was conducted in India showing that vitamin D deficiency may affect the length and regularity of the menstrual cycle (Singh et al, 2021). Moreover, in the United States (US), in another study conducted in 2021, it was shown that deficiency in vitamin D has been associated to specific physical premenstrual symptoms (PMS) such as breast fullness and generalized aches and pains (Alkhalaf et al, 2021).…”
Section: Medical Sciencementioning
confidence: 99%
“…Ultimately, 16 eligible studies were assessed, and eight of these were included for a full review. 14,17,20,[24][25][26][27][28] Articles were excluded for the following reasons: duplicate paper, irrelevant title, wrong study design and population based on abstracts, and wrong outcomes based on full-text review. Figure 1 illustrates the overall process of the study selection.…”
Section: Study Selectionmentioning
confidence: 99%
“…Six of the eight reviewed studies were observational studies. 14,17,20,24,27,28 and the rest were randomized control trials (RCTs). 25,26 The studies included a range of 60 to 1,133 women aged 12 to 55 years.…”
Section: Study Characteristics and Quality Assesmentmentioning
confidence: 99%
See 1 more Smart Citation